A Comparison of the Metabolome of Male and Female Drosophila melanogaster - Zhang, Rong; Zhang, Tong; Korzekwa, Dominika; Al-Johani, Shadi; A.T. Dow, Julian; G. Watson, David (Current Metabolomics, 2014)
Metabolite profiles of ten batches of male and female Drosophila melanogaster were compared using three different chromatographic methods interfaced to an Orbitrap Exactive mass spectrometer. Several thousand features were observed and were reduced after data extraction and careful checking of around 390 metabolites excluding lipids. Chromatographic traces for these metabolites are presented as supplementary information. There were many significant differences between male and female flies. Female flies contained much higher levels of methylated lysines and methylated arginine suggesting differences in histone metabolism. In addition, there were differences in the methylation of nucleosides, and Sadenosylmethionine metabolism. Differences in the methylome may relate to the requirement of compensation for the single X chromosome present in males since methylated histones inhibit gene transcription. Nucleoside phosphate levels were elevated in female flies which may relate to increased requirement for DNA biosynthesis for egg production. A series of acylated amino acids previously observed in Drosophila was further characterised and these metabolites were present to a much greater extent in female flies and may be associated with the microbiome.
Keywords: methylation